Landscape intervention in the Hospital for Covid-19 pandemic in Madrid - Jorge, Cristina (Landscape Architecture and Art, 2021)
From Design with Nature of Ian L. McHarg to The Origin of Eukaryotic Cells of Lynn Margulis, the role of the microorganisms in the cycle of life, health, and disease, and in climate change constitutes the life support system of the biosphere. The micro-parklands of the Emergency Hospital in Madrid create a natural system of prefabricated elements following the aim of rapid implementation, isolation, and protection taking as reference the simple integrated system of living microorganisms. These micro-enclosures provide circular areas where patients, visitors, or healthcare professionals can meet in secret places surrounded by trees and shrubs or long green islands where they can walk around. The landscape architecture project has a surface of 7,434 sqm and occupies a plot of 69,791 sqm located in the Hortaleza district of Madrid. Belonging to the previous City of Justice project on the north side of the Institute of Legal Medicine, the plot, which is trapezoidal with a drop of 4,5 meters, is destined for a public hospital constructed in four months during the Covid-19 pandemic. Due to dry climatic conditions, adapted species with low water demand have been selected reducing the risk of allergies or respiratory problems. The topography has been modified to conserve rainwater and direct it to green areas that act as sponges that reduce runoff, store water, remove sediment and pollutants and release it into other ecosystems. There is no separation between soft scape (planting) and hard scape (soil) in the intervention, both are soft and porous and have macro and micro living beings. Following the references of these books, creativity and destruction as real phenomena both have attributes such as fitness and unfitness in the evolutionary way or health and disease. The vital system of living organisms (creativity) and viruses (destruction) has guided the design and distribution of these external areas that intend to prevent infections in the open air, as part of the mutation and adaptation process.